Resveratrol protects against irradiation-induced hepatic and ileal damage via its anti-oxidative activity - VELİOĞLU ÖĞÜNÇ, AYLİZ; YEGEN, BERRAK; ERZİK, CAN; ÇETİNEL, ŞULE (TAYLOR & FRANCIS LTD, 2009)
The present study was undertaken to determine whether resveratrol (RVT) could ameliorate ionizing radiation-induced oxidative injury. After a 10-days pre-treatment with RVT (10 mg/kg/day p.o.), rats were exposed to whole-body IR (800 cGy) and the RVT treatment was continued for 10 more days after the irradiation. Irradiation caused a significant decrease in glutathione level, while malondialdehyde levels, myeloperoxidase activity and collagen content were increased in the liver and ileum tissues. Similarly, plasma lactate dehydrogenase and pro-inflammatory cytokine levels, 8-hydroxy-2'-deoxyguanosine and leukocyte apoptosis were elevated, while antioxidant-capacity was reduced in the irradiated rats as compared with the control group. Furthermore, Na-1, K-1 -ATPase activity was inhibited and DNA fragmentation was increased in the ileal tissues. Resveratrol treatment reversed all these biochemical indices, as well as histopathological alterations induced by irradiation. In conclusion, supplementing cancer patients with adjuvant therapy of resveratrol may have some benefit for a more successful radiotherapy.
Keywords: Irradiation; lipid peroxidation; glutathione; myeloperoxidase; resveratrol; INDUCED OXIDATIVE STRESS; INDUCED LUNG INJURY; IONIZING-RADIATION; RED WINE; RATS; MECHANISM; CANCER; CELLS; ORGAN; ACID